Effect of Thermomechanical Treatment Combination on Electrochemical Behavior of Nickel Free-Stainless Steel Fe-10Mn-16Cr-3Mo - Miftakhur - Rohmah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2022)
Nickel-free stainless steel has emerged as an implant due to its excellent mechanical and corrosion properties. The toxic effect of Nickel ion released in the conventional SS316L need to be addressed. As one of austenitizing elements used as Nickel substitution, Nitrogen is an important alloying element to improve the strength and resistance to pitting susceptibility. In this research, the Nickel-free Fe-10Mn-16Cr-3Mo stainless steel has been developed. The effect of thermomechanical treatment consists of hot forging, hot rolling, cold rolling, and their combination followed by solution treatment on the electrochemical properties was further investigated. The corrosion resistance of Fe-10Mn-16Cr-3Mo was evaluated by the EIS and polarization test in Hank’s solution at 37℃. A ferrite-austenite duplex structure was identified by microstructural investigation, with indistinct intermetallic phase at homogenized sample. Meanwhile, fully recrystallized grains and twinning structures were formed at thermomechanical samples, indicating in dynamic recovery and dynamic recrystallization. Furthermore, the potentiodynamic parameters demonstrates the protective oxide in all samples. However, sample #5 shows a lower current density, around 0.184 µA/cm2, compared to other samples, indicating more protective passive film. In addition, the corrosion potential of sample #5, around 198 mV leading to higher corrosion resistance up to 0.02894 mmpy.